Systematic Literature Review : Perbedaan Penggunaan Unit Indikator Dalam Menentukan Resiliensi Ekosistem Terumbu Karang : Systematic Literature Review: Variations in Indicator Units for Assessing Coral Reef Ecosystem Resilience - Muhammad Fahrul Barcinta; Zurnida Haulussy; Fahrul Rozy Fakaubun (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2026)
Coastal areas are dynamic social–ecological systems that are highly vulnerable to global and local environmental pressures, requiring resilience-based management, particularly for coral reef ecosystems. This study aims to identify and synthesize resilience indicators and methodological approaches using a Systematic Literature Review (SLR). Data were collected from Scopus and Google Scholar via Publish or Perish, yielding 172 initial articles, which were filtered down to 10 relevant studies. The results show that core ecological indicators—live coral cover, herbivore biomass, juvenile recruitment, macroalgae cover, and structural complexity—are consistently used as primary determinants of resilience. Anthropogenic pressures and socio-economic conditions also influence adaptive capacity but do not replace biophysical factors. However, variations in measurement methods, normalization, and indicator weighting limit cross-study comparability. Therefore, a standardized, transparent, and comparable assessment framework is needed. In conclusion, standardizing indicators and methods is essential to improve assessment reliability and support sustainable coral reef management and conservation.